Narrativas sobre limites y comunicación en un grupo de padres y madres cabeza de familia con hijos que presentan bajo rendimiento académico (2020)
Studies on academic performance and family dynamics are of great relevance and complexity, which is why special attention has been given in recent years. This research will present an analysis of communication and the limits that arise within family dynamics in a group of mothers and fathers who are heads of households with children who present low academic performance, with this aim to identify the type of communication that is they develop within the family system, the characteristics of the limits that are formed in these groups of families, as well as the elements that make up the content of the message. In order to investigate this topic, a narrative, qualitative study is implemented with 5 groups of parents with children who have low academic performance, who are in grades 8 and 9, implementing in-depth interviews. Finally, the results were obtained that highlight the type of communication that predominates within the family systems, in addition to the characteristics that are presented at the time of forging the limits or rules in the family environment and the emotional content that is found within the messages that they exchange the members of the family system.